2020
DOI: 10.1177/0267659119897746
|View full text |Cite
|
Sign up to set email alerts
|

Use of extracorporeal membrane oxygenation in postcardiotomy pediatric patients: parameters affecting survival

Abstract: Aim: We aimed to investigate the risk factors affecting survival after extracorporeal membrane oxygenation use in pediatric postcardiotomy patients. Methods: One hundred thirty-three consecutive patients who underwent surgery for congenital heart disease who needed extracorporeal membrane oxygenation support were retrospectively analyzed. Results: In all, 3,082 patients were operated, of which 140 patients (4.54% of the total number of operations) needed extracorporeal membrane oxygenation. Eighty (60.1%) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Regarding the associated malformations, patients with trisomy 21 make up to 20% of syndromic patients needing ECMO treatment ( 11 ). Furthermore, studies show that the presence of Down and DiGeorge syndrome does not affect survival after ECMO ( 24 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the associated malformations, patients with trisomy 21 make up to 20% of syndromic patients needing ECMO treatment ( 11 ). Furthermore, studies show that the presence of Down and DiGeorge syndrome does not affect survival after ECMO ( 24 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies show that the presence of Down and DiGeorge syndrome does not affect survival after ECMO ( 24 , 31 ). Conversely, Ergun et al found that the presence of a syndrome increased mortality ( 11 ). In our study, two of our 16 patients (12.5%) had associated medical conditions, and both were in the non-survivor group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfusion was performed if hematocrit levels were lower than 30%, with platelet count lower than 50000 / µL. We described our ECMO protocol in detail in our previous article 4,5 .…”
Section: Ecmo System and Protocolmentioning
confidence: 99%
“…ECPR, a rapid ECMO deployment procedure replacing conventional CPR, was only performed in 618 patients. Four studies reported the successful use of veno-venous ECMO when patients had an adequate cardiac function and needed lung support (29,34,35,47). Ventricular venting was only reported in 6 studies (11,13,15,18,19,31).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%